Identifying intangible and biocultural heritage elements toward environmental understanding: engaging stakeholders through art - Martha B Lerski (Ecology and Society)
Grounded in a case study in Barbuda in the Caribbean, this research examines sustainability from the perspective of what arts and heritage can contribute to community engagement and local and broader understandings about the environment. This article documents a growing body of literature recognizing the role of arts and culture, including local knowledge and traditional ecological knowledge (TEK), in climate change endeavors. Art and TEK present expansive world views. Contextual information situates research done on the island of Barbuda pre- and post-Hurricane Irma. Visual arts workshops engaged community members in mixed methods research. Results documented cultural elements, particularly intangible and biocultural heritage, inclusive of a democratically selected land tenure system. Workshops involved local residents in a process of identifying cultural and ecosystem priorities, and conservation strategies. Rights holders identified relevant heritage elements and traditions. The research generated hypotheses regarding arts-based research in climate adaptation or mitigation.